2021
DOI: 10.1074/jbc.ra120.015187
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical properties of human myosin-1C are modulated by isoform-specific differences in the N-terminal extension

Abstract: Myosin-1C is a single-headed, short-tailed member of the myosin class I subfamily that supports a variety of actin-based functions in the cytosol and nucleus. In vertebrates, alternative splicing of the MYO1C gene leads to the production of three isoforms, myosin-1C0, myosin-1C16 and myosin-1C35, that carry N-terminal extensions of different length. However, it is not clear how these extensions affect the chemomechanical coupling of human myosin-1C isoforms. Here, we report on the motor activity of the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…Binding of surface-attached a-actinin to A-Tpm iScience Article cofilaments leads to a reduction in the filament sliding velocity as the external load increases with the concentration a-actinin and impedes the driving force of myosin (Figure 4C). We have previously observed that the load-dependent changes in the sliding velocities of Myo1C 0 -DTH1 are best described by a tensionsensing mechanism that includes a force-dependent and a force-independent transition (Giese et al, 2020). The resulting force-velocity dependences (Figure 4D) indicate a marked reduction in motive power generation in the presence of actin cofilaments containing Tpm1.7 or Tpm3.1.…”
Section: Ll Open Accessmentioning
confidence: 84%
See 4 more Smart Citations
“…Binding of surface-attached a-actinin to A-Tpm iScience Article cofilaments leads to a reduction in the filament sliding velocity as the external load increases with the concentration a-actinin and impedes the driving force of myosin (Figure 4C). We have previously observed that the load-dependent changes in the sliding velocities of Myo1C 0 -DTH1 are best described by a tensionsensing mechanism that includes a force-dependent and a force-independent transition (Giese et al, 2020). The resulting force-velocity dependences (Figure 4D) indicate a marked reduction in motive power generation in the presence of actin cofilaments containing Tpm1.7 or Tpm3.1.…”
Section: Ll Open Accessmentioning
confidence: 84%
“…6 iScience 25, 104484, July 15, 2022 iScience Article to 0.07 G 0.01 s À1 in the presence of cofilaments containing either Tpm1.7 or Tpm3.1. We have previously shown that in the presence of bare F-actin k cat , the maximum value of ATP turnover in the presence of saturating actin concentrations, is reduced from $0.37 s À1 at 37 C to 0.09 G 0.02 s À1 at 20 C (Giese et al, 2020). Thus, in the absence and presence of Tpm isoforms, the observed differences between the rate limiting step k +4 and k cat are primarily owing to the different temperatures at which the transient and steady-state kinetics experiments were performed.…”
Section: Ll Open Accessmentioning
confidence: 97%
See 3 more Smart Citations